Chemical constituents from leaves of aquilaria subintegra - Saripah Salbiah Syed Abdul Azziz (Tanjung Malim, 2023)
Chemical constituents from leaves of aquilaria subintegra by Saripah Salbiah Syed Abdul Azziz